A new Boulenophrys species (Anura, Megophryidae) from the coastal hills of eastern Fujian Province, China - Shi-Shi Lin; Hong-Hui Chen; Yuan-Hang Li; Zhao-Ning Peng; Zhao-Chi Zeng; Jian Wang (ZooKeys)
A new species of the genus Boulenophrys is described from the coastal hills of eastern Fujian Province, China. The new taxon can be distinguished from all recognized congeners by a combination of discrete morphological character state differences and genetic divergences in the combined mitochondrial 16S + CO1 genes. We also provide a map showing the distribution pattern of Boulenophrys species in Fujian and a provincial-specific key, which will aid their conservation by helping the local authorities accurately identify species during field identifications and data collection efforts.